ANALISIS PRODUKSI DAN KOMPARATIF ANTARA USAHATANI JAGUNG HIBRIDA DENGAN NONHIBRIDA DI KECAMATAN PALOLO KABUPATEN SIGI - Made Antara (Agroland: Jurnal Ilmu-ilmu Pertanian, 2010)
This research aimed to identify : (1) factors influencing production of hybrid and non-hybrid corn, and (2) the disparity of income between hybrid and non-hybrid of corn agribusiness. The research was conducted in 3 villages of Palolo Subdistrict,  namely: Bobo, Bunga and Berdikari. Sixty six farmers (34 hybrid corn farmers and 32 non-hybrid corn farmers) were chosen as sample respondents based on randomized sampling. The results of the research showed that all variables observed were found to influence the hybrid corn production, except for experience in agribusiness. Similarly, production of the non-hybrid corn was also influenced by all variables, except for the amount fertilizer used and experience in agribusiness. The income of the hybrid corn agribusiness for one planting season was IDR 4,882,225.79 ha-1 higher than IDR 2,691,452.10 for the income of non-hybrid corn agribusiness